The Modern World and the History: The Perspective of a Man - Fathor Rasi (Budapest International Research and Critics University, 2019)
The modern man comes to revolt against heaven, they have made a foundation of knowledge without and free from the light of intellect guidance (Intellectus in Latin and Nous in Greek which has higher position than reason). This article argues that, the intellect itself will enable to know who himself and enable him to access direct and immediate knowledge of himself, while reason as only a reflection of intellect itself. Denying the existence of intellect means rely on the reason only to get the data through the external sense. Modern civilization in the West has built the new concept of man but unfortunately excluding the most essential part of man himself. It can be concluded that The human as microcosm has responsibility to maintain and care to the nature. The nature is no longer regarded as enemies to dominated and exploited but as friends in a spiritual odyssey and helper for man who has the spiritual journey through the forms of the world of spirits which become the source of humanity and the nature itself.